2014
DOI: 10.5897/ajb2013.13035
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular evaluation of some Egyptian pomegranate cultivars

Abstract: Six Egyptian pomegranate (Punica granatum L.) cultivars were characterized by fruit characteristics (physical and chemical) and two molecular markers; Inter simple sequence repeat (ISSR) and amplified fragment length polymorphism (AFLP). Genetic diversity of the pomegranate genotypes was evaluated. Physical fruit traits were determined (weight, volume and diameter), calyx [diameter, length (mm) and Carpels number], fruit firmness (Newton), peel as (weight and thickness), arils weight (g), volume of juice (ml),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…However, the increasing in juice TSS was referred to the loss water of fruit then leading to increase concentration of the soluble solids. The obtained data were agreement with those found by (Koksal, 1989, Nanda et al, 2001, Omayma et al, 2014.…”
Section: B-chemical Properties 1-total Soluble Solids (Tss %)supporting
confidence: 92%
“…However, the increasing in juice TSS was referred to the loss water of fruit then leading to increase concentration of the soluble solids. The obtained data were agreement with those found by (Koksal, 1989, Nanda et al, 2001, Omayma et al, 2014.…”
Section: B-chemical Properties 1-total Soluble Solids (Tss %)supporting
confidence: 92%
“…Gowda et al (2009) [12] observed that in additional investigations conducted in Egypt, Manfalouty cultivar fruits had the greatest significant total soluble solids (15.80°Brix), whereas fruits of the Araby cultivar yielded the lowest total soluble solids (14.63°Brix). Additionally, SSC content for the Hegazy cultivar ranged from 16.01°Brix to 12.55°Brix, according to Ismail et al (2014) [15] in Egypt.…”
Section: Evaluation Of Fruit Characteristicsmentioning
confidence: 99%
“…In many studies, molecular marker techniques such as RAPD, SSR (Orhan et al, 2014;Caliskan et al, 2018), and ISSR have been utilized (Jbir et al, 2014). The ISSR molecular marker technique has been found useful for examining genetic relationships among pomegranate genotypes and varieties, mainly due to its ability to generate a higher number of polymorphic bands (Ismail et al, 2014;Heidari et al, 2016;Almiahy and Jum'a, 2017;Hajiyeva et al, 2018;Al Mousa et al, 2019;Karapetsi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%